Penerapan Model Pembelajaran Kooperatif Tipe STAD dalam Meningkatkan Hasil Belajar IPA Siswa Kelas VI - Riska Azizah; Rahmi Inri Sam; Nasrah Nasrah; Lidan Lidan (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
This research is motivated by the learning outcomes of class VI students at SD Negeri 30 Sumpang Bita which still need to be improved. The purpose of this study was to find out whether cooperative learning type STAD can improve science learning outcomes in class VI students at SDN 30 Sumpang Bita. This research is a class action research (Classroom Action Research) which includes planning, implementation, observation and reflection. This research lasted for 2 cycles. The research subjects were 18 students in class VI at SD Negeri 30 Sumpang Bita for the 2022/2023 academic year. Data collection techniques through tests, observation and documentation. This research uses descriptive qualitative. The data obtained from observation sheet data and student tests were analyzed by calculating the percentage of all observed indicators. The results showed that the motivation and learning outcomes of students after the implementation of the STAD type cooperative learning model showed that the average of all indicators both from the aspect of learning motivation and learning outcomes increased. This is indicated by an increase in the average percentage of observation sheets in cycle I by 67%. In cycle II there was an increase of 89% which met the Minimum Completeness Criteria.